Effect of Near Work on Binocular Vision Measurements in Adults with Convergence Insufficiency. - Yi Pang; Gabriel, Helen; Frantz, Kelly A. (Optometry & Visual Performance, 2015)
Background: Convergence insufficiency (CI) is a common binocular vision disorder. A common characteristic of CI is that patients have more symptoms, such as eyestrain and headache, after close work. The purpose of this study was to determine whether 30 minutes of reading affects the binocular and accommodative measurements used in the diagnosis of CI. Methods: Eighteen normal adult subjects and eighteen adult CI subjects (symptomatic and asymptomatic) were recruited. None of the CI subjects had accommodative insufficiency. The following measurements were made: distance and near cover test, near point of convergence (NPC) with accommodative target (AT), NPC with transilluminator and red lens (RL), near positive fusional vergence (PFV), and accommodative amplitude. Subjects were then asked to read a book for 30 minutes, immediately followed by repeated administration of the above tests by the same examiner. Statistical analysis was performed using a Student's paired t-test to compare the measurements before and after reading. Results: In the CI group, the mean phoria at near changed from 7.06Δ exophoria to 6.56Δ exophoria after reading for 30 minutes. Mean NPC break with AT changed from 9.58 cm to 11.25 cm. With RL, an average increase from 12.56 cm to 13.93 cm occurred for NPC break. Mean PFV break decreased from 17.22Δ to 15.56Δ. Mean amplitude of accommodation (OD) changed from 7.46 to 7.56 diopters. Only the change in NPC break with AT after reading was statistically significant (P = 0.007). There were minimal changes in clinical measurements after reading in the normal subjects. Conclusion: Half an hour of reading had a statistically significant effect on the NPC break with AT but not on other binocular vision measurements in subjects with CI. It is unknown whether a longer period of reading would have a greater effect.